PELATIHAN PEMROGRAMAN KOMPUTER MENGGUNAKAN VISUAL BASIC UNTUK SISWA SMK PL LEONARDO KLATEN - Sambada, Rusdi; Sugiharto, Budi; Purwadianto, Doddy (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Pangudi Luhur Vocational School students are of productive and innovative age. So it is necessary to get additional knowledge to increase the power of creativity to face increasing competition. Computer Programming using Visual Basic is an effort to increase creativity. Visual Basic is integrated into Microsoft Excel software, almost always present on the computer. Computer programming is done to help with repetitive calculations, especially in the design of machine elements. It is hoped that vocational students will be more creative and develop according to the field to be occupied. In addition, the output targets for this service are training modules and submitting articles to community service journals